Efficacy of and Resistance to Rifaximin-based Quadruple Therapy in Eradication - Hyun Soo Kim; Hyuk Yoon; Dong Woo Shin; Dong Jun Oh; Mingu Kwon; Yoon Jin Choi; Cheol Min Shin; Young Soo Park; Nayoung Kim; Dong Ho Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims The treatment options for Helicobacter pylori (H. pylori) infection are in a state of flux: traditional triple therapies have started to fail, and new treatments are unable to achieve optimal eradication rates. Rifaximin and rifabutin are new antibiotics. The aim of this study was to evaluate the efficacy and safety of adding rifaximin to the standard triple regimen and of a rifabutin-based triple regimen as a rescue therapy for H. pylori eradication. Materials and Methods We enrolled 27 H. pylori-positive patients who were treated with a proton pump inhibitor, amoxicillin, clarithromycin, and rifaximin for 14 days. H. pylori eradication was assessed by a 13C-urea breath test performed 4 weeks after therapy completion. The efficacy of the therapy was based on intention-to-treat (ITT) and per-protocol (PP) analysis. We also investigated the resistance rate, compliance, and side effects associated with rifaximin therapy. Minimal inhibitory concentrations and resistance to rifabutin were evaluated using the agar dilution method. Results Of the 27 patients, 22 completed the treatment protocol with 100% compliance; five patients withdrew. The ITT and PP eradication rates for the rifaximin-containing quadruple therapy were 70.4% (19/27) and 86.3% (19/22), respectively. Adverse events were observed in five of 22 patients (22.7%). The resistance rates to rifaximin and rifabutin were 66.7% (2/3) and 0% (0/3), respectively. Conclusions The findings of this study show the limitations of rifaximin-based quadruple therapy and suggest the benefits of a rifabutin-based rescue regimen in South Korea.